The cmparative analysis on muscles of short and long track speed skating athletes - Xia, J. (Applied Mechanics and Materials, 2011)
The knee and ankle muscle strength of excellent male skating athletes is measured and analyzed by Cybex isokinetic testing system. Based on the features of athletes` muscles strength, the study aims to find if there are differences and shortages between long track and short track speed skating athletes and whether they can learn from each other in the training, then to make the further discussion on the event itself. The main conclusions are as follows: 1. In the index of maximum strength, the torque/BW features of knee and ankle of the short track athletes are more fit the law of skating event, while the long track athletes do good in low speed, but opposite in high speed. The long track skaters need to improve the strength in high speed. 2. In the index of flexor-extensor, both long and short-track are lower than the recommended values, especially the short track. The two groups need to improve the strength of flexor muscles and to keep balance and coordinate of knee muscles. 3. In the index of acceleration, the power values of long track skaters are higher than short track skater`s, except left extensor muscles. The left extensor muscles of long track skaters are lower than their right ones, and should improve the balance of both legs. The short track skaters need to improve the powers of left and right knees in all speeds.